Trade, poverty eradication, and the sustainable development goals - Brambilla, Irene (2016)
This paper investigates if trade can help achieve the United Nations Sustainable Development Goal of poverty eradication using microeconomic and macroeconomic mechanisms and the effects of trade and trade policy on consumer prices, producer prices, and wages. As these mechanisms affect the real income of households, they determine the likelihood that a household may be lifted out of or pushed into poverty. The impacts of trade on growth and longer-term consequences of trade liberalization were also analyzed using data from African countries. While there is sound evidence that trade can be pro-poor, there is significant heterogeneity in the poverty impacts of trade, both across households and countries. This highlights the importance of complementary policies such as infrastructure, trade facilitation, and social protection.